2016
DOI: 10.1159/000442995
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Zone Index as a Predictor of the Efficacy of α-Blocker and 5α-Reductase Inhibitor Combination Therapy in Korean Patients with Benign Prostatic Hyperplasia

Abstract: Introduction: We investigated the value of the transitional zone index (TZI) for predicting treatment response to combination therapy involving α-blockers and 5α-reductase inhibitors for benign prostatic hyperplasia (BPH). Materials and Methods: Symptomatic BPH patients (n = 118) were randomized to receive 0.2 mg tamsulosin alone or with 0.5 mg dutasteride daily for 12 months. The TZI, International Prostate Symptom Scores, maximum urinary flow rates (Qmax), postvoid residual urine volumes, and pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Yet another study reported a strong correlation when the cut-off value for TZI was 0.50 (6). The same cut-off for TZI, 0.50, was also confirmed in the most recent study (21). Our cut-off values 0.40 and 0.45 are in line with the above-cited studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Yet another study reported a strong correlation when the cut-off value for TZI was 0.50 (6). The same cut-off for TZI, 0.50, was also confirmed in the most recent study (21). Our cut-off values 0.40 and 0.45 are in line with the above-cited studies.…”
Section: Discussionsupporting
confidence: 91%
“…There is one more recent study on the same subject. In this study, it is reported that TZI ≥0.50 has a strong correlation with MFR improvement (21).…”
Section: Discussionmentioning
confidence: 60%
“…No significant differences were found in terms of Hb, Hct, MVD, and VEGF in prostates of <50 mL. Thus, the prostate volume and even the transition zone index [35] should be taken into account before decision making. There are also some surgical alternatives to medication.…”
Section: Discussionmentioning
confidence: 95%
“…Pharmacotherapy based on polytherapy used solifenacin and tamsulosin also communicated with progress in patient detailed outcomes such as urinary nerve growth factor and creatinine levels (23). Investigation of Choi et al (24) showed that combination therapy comprising of α-blockers and 5α-reductase inhibitors in patients with a transitional zone index (TZI) of ≥ 0.5 is expected improvement linked to greater maximum urinary flow rates (Qmax). As a final point according to the published articles tamsulosin-therapy based on inter-and intra-individual assumption for BPH, seem to be safe and effective to improve the related symptoms and quality of life in patients.…”
Section: Resultsmentioning
confidence: 99%